Transient Simulations of CPR1000 Nuclear Power Plant Implementing Advanced Mechanical Shim Control System. (2nd December 2018) - Wu, Shifa; Wan, Jiashuang; Song, Hongbing; Wei, Xinyu; Zhao, Fuyu; Revankar, Shripad
Abstract: A novel concept of implementing the advanced mechanical shim (MSHIM) control system on the improved Chinese Pressurized Water Reactor (CPR1000) is proposed. The reactor power control system of CPR1000 is redesigned to adopt the MSHIM control system while the other parameters and control systems remain unchanged. To investigate the control performance and safety margins of this reconfiguration, the CPR1000 Full-Scope Simulation Platform (CFSSP) is first developed in MATLAB/Simulink with relevant control systems and protection system considered. The CFSSP consists of the one-dimensional nodal core model, the nonequilibrium three-region pressurizer model, the lumped-parameters dynamic model of U-tube steam generator with movable boiling boundary, and the balance of plant model. Based on the CFSSP, operational transients of step and linear turbine load changes were simulated and analyzed. The simulation results agree well with physical laws and the control performance is satisfactory. All key parameters are kept within acceptable ranges with enough safety margins and thus the protection system is not triggered. Therefore, the CPR1000 nuclear power plant implementing the MSHIM control system can safely sustain the ±10% full-power (FP) step changes and ±5% FP/min linear changes of load transients. This study can serve as a reference for the MSHIM control system application to pressurized water reactors.